SITUATIONAL CRISIS COMMUNICATION THEORY PADA HUMAS PT KAI DAOP 1 JAKARTA DALAM MENANGANI GANGGUAN OPERASIONAL - Wianda Tika; David Rizar Nugroho; Salsabila Fathifalah; Ailsha Shabila; Muhammad Rizky Maulana (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2025)
Crisis is a condition that can threaten the operational sustainability and reputation of a company unexpectedly. This study aims to examine the crisis communication strategy implemented by the Public Relations of PT Kereta Api Indonesia (Persero) Daop 1 Jakarta in handling operational disruptions due to flooding that occurred in Semarang in January 2025. The research used a descriptive qualitative approach through in-depth interviews and literature study. The results showed that this crisis was classified as a victim cluster according to the Situational Crisis Communication Theory (SCCT) framework. This is because natural disasters occur outside the company's control. PT KAI implemented three main strategies, namely diminish to explain that the disruption was caused by external factors, rebuild by apologizing and compensating passengers, and bolstering to strengthen a positive image through responsive and empathetic communication. PT KAI also optimized communication channels such as social media, KAI Access application, and WhatsApp Blast to reduce public unrest. These findings show the importance of fast, transparent, and coordinated communication in maintaining public trust and strengthening relationships with stakeholders. The right crisis communication strategy not only reduces negative impacts, but also strengthens the organization's readiness to deal with similar crises in the future.